Cross-cultural communication - Hurn, Brian J (Palgrave Macmillan, 2013)
Includes bibliographical references and index; What is cross-cultural communication? -- Key thinkers in cross-cultural communication (1) -- Key thinkers in cross-cultural communication (2) -- The international use of English -- Developing cross-cultural communication skills -- Selection and preparation for foreign assignments -- Leadership across cultures -- International team building and teamworking -- The effect of culture on international negotiations -- Multiculturalism and diversity -- Globalization and its effect on culture -- Cultural diplomacy and nation branding -- Transfer of skills, technology and knowledge -- Cultural profiling and classification -- Teaching cross-cultural communication; "Offers a deeper understanding of the need for effective cross-cultural communication and cultural awareness by those engaged in working in the international environment. This area is of increasing importance in the diverse and multicultural world where such effectiveness plays a major part in achieving competitive advantage. The emergence of India and China as future economic giants and the increasing influence of globalization have led to greater emphasis on the cultural dimensions of international business, diplomacy and international relations. This volume identifies the barriers to effective cross-cultural communication and suggests practical strategies to overcome them. Key aspects of this include the identification of the skills and competencies required for success, the personnel selection methods and the options for pre-departure cultural training. The authors provide practical examples from their own experience in over 60 countries and from discussion with professional colleagues and international students."--Publisher's website